The Role of Colour Representation in Religion: The Case of Islam and Christianity - Abamwa, Oghenekevwe E; Ottuh, Peter O (dialektika kontemporer, 2024)
This paper analyzes the function of colours in religion, particularly Christianity and Islam. The purpose is to investigate how colours are utilized in religious rites, practices, and iconography and how these linkages influence religious comprehension and behaviour. A qualitative approach is utilized in the research, which includes the examination of religious writings, artwork, and rituals, as well as interviews with religious researchers and practitioners. Even though both religions use colour to communicate theological ideas and moral teachings, the findings indicate that the meanings of specific colours frequently differ. This reflects the different cultural contexts in which Islam and Christianity are situated. In addition, the study highlights the significance of colour representations of religious aesthetics and how they affect spiritual participation. Among the recommendations is the need for additional research into the interaction of colour, religion, and cultural interchange, particularly in nations that are becoming increasingly multicultural.